Effect of Sabla Programme on Health Status of Women in Bihar - Kumari, Arunima; Kumari, Rekha (Indian Journal of Extension Education, 2020)
With the malnourished or unhealthy women population, all-round development of a society cannot be imagined.Â About half of Indiaâ€™s adolescent girls are anemic, while nearly half of the girls are also underweight. Case of Bihar is worse than the national average. In rural Bihar, only 46.4 per cent women are literate, this increase their chances of being forced into child marriage (40.9% women aged between 20-24 years are married before 18 yrs)Â and subsequently, there is high risk of early pregnancy. These young women give birth to underweight children resulting in high Infant Mortality Rate (IMR). Only 3 per cent of rural women (overall 6.6%) receive full antenatalÂ check-up and this cannot be expected to reduce the MMR and IMR. The study was conducted in VaishaliÂ district of Bihar to know the status of Sabla programme in improving health of the women.